Penerapan Sulam Pita Dan Anyaman Sebagai Hiasan Pada Busana - Edi Suwasana; Aisyah Dewi Sri Annisa (Garina, 2023)
Ribbon embroidery is an embroidery art that uses ribbons as the embroidery material, the development of ribbon embroidery to be applied to the clohting is still something that is rare because usually ribbon embroidery is only used in the manufacture of household linen or just as decoration. Likewise with webbing which is usually found on objects made of bamboo, because woven is rarely used in decoration on clothing. Destination making this report to find out the process of making decorated clothes using ribbon and woven embroidery. The methodology. The methodology used is Research and Development (R&D) method, data analysis using Analysis Descriptive. Making ribbon and woven embroidery that is applied to clothing through several stages, namely: 1) determining the fashion design, 2) the process of embroidering robbon, 3) weaving process, 4) validation, 5) sizing on the model, 6) pattern making, 7) cutting material, 8) making seams, 9) pressing, 10) sewing process, 11) finishing. The process of making clothing needs to be done carefully, to produce appropriate clothing. On sewing the skirt with refence to the pattern Singo Sato should be done carefully when sewing curved, because it can make the fabric stretchy if it’s too tight holding it in the sewing process. And it will make the stitching result not according to size.